Pengaruh Free cash flow Dan Pertumbuhan Perusahaan Terhadap Kebijkaan Dividen Dengan Good corporate governance Sebagai Variabel Moderasi - Fitriya Anjelina; Aranta Prista Dilasari (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The purpose of this study is to determine the effect of FCF and company growth on dividend policy and to determine whether GCG can moderate the relationship between free cash flow and company growth variables on dividend policy. The data analysis methods used in this study are multiple linear regression and moderated regression analysis (MRA). The population in this study was 92 property and real estate companies listed on the Indonesia Stock Exchange in 2020-2024. The results show that FCF, company growth, and GCG have a positive effect on dividend policy. Meanwhile GCG as a moderating variable is proven to be significantly negative and able to moderate the effect of free cash flow and company growth on dividend policy.